94+7x=102+6x

Simple and best practice solution for 94+7x=102+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 94+7x=102+6x equation:


Simplifying
94 + 7x = 102 + 6x

Solving
94 + 7x = 102 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
94 + 7x + -6x = 102 + 6x + -6x

Combine like terms: 7x + -6x = 1x
94 + 1x = 102 + 6x + -6x

Combine like terms: 6x + -6x = 0
94 + 1x = 102 + 0
94 + 1x = 102

Add '-94' to each side of the equation.
94 + -94 + 1x = 102 + -94

Combine like terms: 94 + -94 = 0
0 + 1x = 102 + -94
1x = 102 + -94

Combine like terms: 102 + -94 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| 3.6(4+5x)-3.4=11 | | .9x+.2*90=.8(90+x) | | 2x+4(x-20)=220 | | 10y=6x-10 | | 9x^2-2x+5=0 | | 4x^2-8x+4=56 | | 4y-5+y+26=7+5y+23-3y | | 2m+3n=19 | | 53+6x=61+4x | | X+0.04x=31.2 | | 1.5x+3.7=3.4x-2 | | 4x+4(x-20)=424 | | 4cos(3x)=3 | | 20x+7=2x+25 | | 4m-3n=-7 | | x+x+(x+20)+(x+20)=300 | | x+(2x-6)+(x+6)=64 | | -(-x+2)=-2.2 | | 4+6x=5x+2 | | x+q=jforq | | x+9y^2=0 | | x+20-5x=7(3+x)-3x | | 3.3(4+5x)-0.2=13 | | (x+4)-2(4-4x)=5(x+3)-3 | | 5x^2=2x+7 | | x^2-800x-12000=0 | | 5x+2-7x=10+20x | | -4.5=1.23 | | 18x+27+21=28x+7-189 | | 20.8x-3(x+0.4)=-36.8 | | 4y-3+y+37=6+8y+34-5y | | x-6=4*x+5-3*x |

Equations solver categories